ChemInform Abstract: Phase Coexistence in NaTaO3 at Room Temperature; a High Resolution Neutron Powder Diffraction Study. Issue 26 (June 2015) - Knight, Kevin S.; Kennedy, Brendan J.
Abstract Time‐of‐flight room temperature high resolution neutron powder diffraction data of NaTaO3 show a phase coexistence of two orthorhombic structures (space groups Cmcm and Pbnm) which are obtained by a phase transition at ≈763 K and which coexist down to room temperature and probably to 0 K.